Factors Affecting Earnings Quality -Survey Study on Companies Listed in Damascus Stock Exchange- (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to identify the factors affecting the quality of earnings, as measured by approaching cash on the one hand, and income smoothing on the other hand.The data is collected using annual financial reports for companies listed in Damascus Stock Exchange. These reports are available on Damascus Stock Exchange website. Using a dataset of 19 listed companies covering the period 2016 to 2020 comprising a total of 95 observations, Panel Data analysis is employed, with the help of the application Eviews 10 and Microsoft Excel 2010.The results showed that there is an inverse effect for each return on assets (ROA), The book value of the share (BVPS), and the positive direct effect of earnings per share (EPS) in earnings quality (EQ1) Measured by approaching cash, while the results of testing the second hypothesis concluded that there is a positive direct effect of the return on assets (RPA), and an inverse effect for each of the ratio of cash to current assets (CAtoCS) and liquidity (LIQ), and earnings per share (EPS), and leverage (LEV) in earnings quality measured by smoothing income (EQ2).